2011
DOI: 10.1016/j.phymed.2010.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene and ellagic acid prevent testicular apoptosis induced by cisplatin

Abstract: The aim of this study was to investigate the possible protective effects of lycopene (LC) and ellagic acid (EA) on cisplatin (CP)-induced testicular apoptosis in male rats. The control group was treated with placebo; LC, EA and CP groups were given alone LC, EA and CP, respectively; the CP+LC group was treated with a combination of CP and LC; and the CP+EA group was treated with a combination of CP and EA. Although CP significantly increased the number of Bax-positive (apoptotic) cells it had no effect on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 16 publications
6
27
1
1
Order By: Relevance
“…In accordance with the reduction of organ weights and sperm concentration, histopathologic examination showed severe degeneration, necrosis in the testis of rats treated with CDDP alone, reflecting the testicular damage directly. Our findings are compatible with report of some researchers (Türk et al, 2011) and confirm the sperm toxic effects of CDDP in rats.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In accordance with the reduction of organ weights and sperm concentration, histopathologic examination showed severe degeneration, necrosis in the testis of rats treated with CDDP alone, reflecting the testicular damage directly. Our findings are compatible with report of some researchers (Türk et al, 2011) and confirm the sperm toxic effects of CDDP in rats.…”
Section: Discussionsupporting
confidence: 94%
“…It has been known that exposure to CDDP (Türk et al, 2011) causes the rise of germ cell apoptotic rates. In the present study, Bcl-2 over-expression.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant effects of EA on cytotoxicity have been evaluated by different studies. For example, it was reported that EA (2 mg/kg) can improve cyclophosphamide (CP)-induced testicular and liver damage by preventing lipid peroxidation and reducing apoptosis through scavenging ROS (Turk et al 2011). It was also reported that EA can regulate Cre and BUN concentrations, elevate the levels of glutathione (GSH), and reduce the necrotic lesions in renal tubular tissues (Atessahin et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that CP has a powerful effect on the destruction of neoplastic cells; it has also some dose-dependent side effects, including; cytotoxicity, nephrotoxicity [14,15] , hepatotoxicity [16] and reproductive toxicity [17] . The CP exposure can break the redox balance of tissues, suggesting that biochemical and physiological disturbances may result from the oxidative stress [18] . The ROS, like singlet molecular oxygen, superoxide anion, hydroxyl radical and hydrogen peroxide are normally produced in the subcellular compartments of testis, particularly within the mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies suggested that some antioxidant substances like lycopene, ellagic acid [18] , royal jelly [23] , melatonin [24] , roselle and ginger [25] and selenium [26] have all ameliorative effects against the CP-induced damages in the male reproductive system. However, in the literature, there appears no study available about the effect of maclura pomifera extract on the spermatological parameters in CP-exposed rats.…”
Section: Introductionmentioning
confidence: 99%